Importancia de la atención del cáncer de próstata con el Programa de Gastos Catastróficos. - Maldonado-Dorantes, Sinue; Arellano-Cuadros, Rodrigo; Martínez-Carrillo, Gumaro; Sandoval-Salazar, Ana Fátima (Boletín del Colegio Mexicano de Urología)
Introduction: Prostate cancer represents one of the main causes of morbidity and mortality in male population in our country, a disease wich has like frequent treatment options the hormonal blockade and chemotherapy due to the stages in which treatment is initiated, which is why The Catastrophic Expenditure Program is essential for the treatment of uninsured patients. Methods: This work presents the results obtained in Hospital Juarez de Mexico with Catastrophic Expenditure Program regarding the treatment of prostate cancer. Results: The follow up of 235 patients was achieved, which presented good Karnofsky at first, however it was deteriorated during treatment in all groups despite a good control of the disease compared to other studies, so the Hormonal blockade is a fundamental part of most treatments. Conclusions: Overcoming the limitantions that imply lack of resources, lack of awareness in the population, medical attention in a "school-hospital" wich don't have the best technological conditions, the Catastrophic Expenditure Program offers to the Mexican population good results in Prostate Cancer treatment. Nevertheless, we need studies in Clinical Stages in specific and long term following to optimize the results even more.